From revolutionaries to citizens : antimilitarism in France, 1870-1914 - Miller-Melamed, Paul, 1964- (Duke backfile, 2002)
A history of the anti-militarist propaganda and activities of the French socialists that seeks to explain why the French left came to accept and in some instances even support World War I.